Women’s changing domestic responsibilities in neoliberal Africa: A relational time-space analysis of Lesotho’s garment industry - Ansell, Nicola; Tsoeu, Seroala; Hajdu, Flora (Gender, Place and Culture, 2015)
Since 2001 when Lesotho embraced the neoliberal African Growth and Opportunities Act that offers preferential access to the US market, its garment industry has expanded dramatically to become the nation’s leading employer. Elsewhere, large-scale employment of women in low-paid factory jobs has entailed spatial restructuring of gender and age relations. Lesotho is a distinctive context, with socio-spatial relations historically adjusted to male labour migration, high levels of contemporary male unemployment and alarming AIDS prevalence. Based on semi-structured interviews with 40 female factoryworkers and 37 dependents, this article applies a relational timespace analysis to explore how financial and spatio-temporal aspects of factory employment articulate to alter women’s relationships with those for whom they have culturally determined responsibilities: their children, those suffering from ill health and their (generally rural) home communities. The analysis highlights that such employment is not merely adding to women’s responsibilities, but transforming how they are able to undertake social reproduction, as practical, social and emotional roles are converted to largely financial obligations. © 2014 Taylor & Francis.
Keywords: 2000 à aujourd'hui; afrique; conciliation famille-travail; lesotho; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; thématiques; travail